The development of style in Malaysian printmaking: 1930-2000 / Mohd Jamil Mat Isa - Mat Isa, Mohd Jamil (2017)
The development of printmaking started as a medium of communication, be it a religious propaganda or as a tool to achieve independence. Printmaking can be classified into several categories, such as relief printing, intaglio, planographic and now in the modern era, is a digital print. Malaysian printmaking has been developing since the Colonial Era (1930s) by Chuah Thien Teng and Abdullah Ariff. Woodcut and linocut are the techniques chosen by them. Later on, other artists explored the medium; they applied more techniques included the latest digital technology. The objectives of this study are to trace on the development of style in Malaysian printmaking, to identify the factors that influence the development of style in Malaysian printmaking and to document the historical development of Malaysian printmaking. This research will use qualitative methods with art historical approach based on the primary and secondary data. The data collected in the form of text from books, exhibition catalogues, and art auction catalogues. The works of printmaking are divided into two main categories, namely the Pre-Independence Era (1930-1957) and Post-Independence Era (1958-2000). This study used theories established by Shapiro, Panofsky, and Feldman to investigate for new findings and new possibilities that can explain the development of Malaysian printmaking, to trace the development of style in Malaysian printmaking as well as to identify the factors that have influenced the style. Malaysian printmaking evolution is related to the local printing industry and began with the demand of relief prints as an illustration in their publications. This research found that the history of local printmaking began when Chuah Thien Teng and Abdullah Ariff explored the techniques in the 1930s in Penang. The establishment of higher institutions, art museums and galleries, artists associations and clubs also completed the development of style in the Malaysian printmaking.